1998
DOI: 10.1590/s0004-282x1998000100006
|View full text |Cite
|
Sign up to set email alerts
|

Sentimentos e reações de pais de crianças epilépticas

Abstract: RESUMO -Objetivos: Identificar as crenças e os sentimentos dos pais frente à epilepsia e relacioná-los com os comportamentos de seus filhos. Avaliar a eficácia dos grupos de pais na diminuição da ansiedade, esclarecimento sobre a doença e comportamentos. Método: Foram aplicados 18 protocolos que avaliaram sentimentos, crenças e comportamento dos pais e filhos, respondidos antes e depois das sessões de grupos de apoio. Resultados: Diante do diagnóstico foram observados mágoa (94,4%), medo (72,2%), susto (27,8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
12

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
(15 reference statements)
0
7
0
12
Order By: Relevance
“…The improved relationship with parents is a result of their changing their behavior toward the child or adolescent. According to Souza et al 30 , parents may have overprotective reactions, exaggerated permissiveness and excessive observation because of the epilepsy, which leads to many restrictions or difficulties in imposing disciplinary boundaries on their children. These behaviors interfere with the patient's QOL.…”
Section: Discussionmentioning
confidence: 99%
“…The improved relationship with parents is a result of their changing their behavior toward the child or adolescent. According to Souza et al 30 , parents may have overprotective reactions, exaggerated permissiveness and excessive observation because of the epilepsy, which leads to many restrictions or difficulties in imposing disciplinary boundaries on their children. These behaviors interfere with the patient's QOL.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that besides the population being less informed about epilepsy, the non-university educated are those that have more stigmas attached to their culture. In a study performed on the parents of epileptic children, it has been demonstrated that 72% of the parents feel fear after the disease is diagnosed in their children, 27% felt scared, 33% sad and anxiety was reported by 27% 19 . Furthermore, problems arose in accepting the disease and the parents expressed rejection (38%), feelings of sorrow (94%) and guilt (11%).…”
Section: Discussionmentioning
confidence: 99%
“…Brazilian publications conclude that people do not have a satisfactory understanding of epilepsy, indicating that the information acquired is superfi cial and that it is necessary to clarify people concerning this issue at all socioeconomic levels 7,15,[19][20][21][22] .…”
mentioning
confidence: 99%
“…A diferença estatisticamente significativa encontrada na dimensão self pessoal mostrou que as mães SXF percebem-se mais inseguras para conduzir suas vidas e com dú-vidas sobre sua competência, corroborando os achados de Souza et al (1998) quando mostraram que mães de crianças epilépticas são mais inseguras e intranqüilas do que os pais. Aqui cabe comentar as questões de gênero no autoconceito reportadas por Carrion, et al (2003).…”
Section: Discussionunclassified